Transmedia storytelling and transmedial worlds: A methodological proposal for the analysis of a media ecosystem, case Civil War - Atarama-Rojas, Tomás (2018)
Transmedia communication has achieved an important evolution and relevance in the last years, being considered by producers and organizations as a key strategy in the development of new projects, known through a diversity of media and platforms. At the same time, this process is influenced by a participative culture made up the prosumers. In this paper, we want to know how and what contribution brings the variety of media in the construction of transmedia worlds. Therefor it is planted as object of study the media ecosystem of Marvel´s Civil War; the comic began as a crossover and now it can be considered one of the transmedia storytelling more complete and complex cases in relation with the multiplicity of media involved.